2016
DOI: 10.20884/1.anprod.2016.18.1.524
|View full text |Cite
|
Sign up to set email alerts
|

Production Systems And Income Generation From The Smallholder Beef Cattle Farming In Yogyakarta Province, Indonesia

Abstract: Abstract. This study was aimed to determine the production systems of beef cattle which can generate the income of smallholder farmers. The study was conducted in Bantul and Sleman Regencies, Yogyakarta Province, Indonesia. In total of 210 beef cattle farmers were involved in semi structural interview. Data was collected in the dry season (July to September) of 2015. Descriptive analysis was carried out for the demographic, social, economic characteristic of respondents and beef cattle farm practices. Enterpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Local butchers generally sell the meat in the regularly organized local markets [ 2 ]. Bakso (meat ball, which is a very popular food in Indonesia) sellers, households, small restaurants and small food processors are the buyers of meat in regular food markets or meat shops [ 24 ]. The demand for meat from large restaurants, hotels, and catering and food industries is met by local production from butchers and feedlots (65%) and frozen meat imports (35%) from Australia (Ahmadi, pers comm).…”
Section: Cattle and Beef Value Chainsmentioning
confidence: 99%
“…Local butchers generally sell the meat in the regularly organized local markets [ 2 ]. Bakso (meat ball, which is a very popular food in Indonesia) sellers, households, small restaurants and small food processors are the buyers of meat in regular food markets or meat shops [ 24 ]. The demand for meat from large restaurants, hotels, and catering and food industries is met by local production from butchers and feedlots (65%) and frozen meat imports (35%) from Australia (Ahmadi, pers comm).…”
Section: Cattle and Beef Value Chainsmentioning
confidence: 99%
“…The results of this study confirmed the results of earlier research, which pointed to male dominance in the beef cattle farming industry. It further revealed that the majority of these farmers are middle-aged and educated mainly to primary school level [16][17][18][19]. The experience of raising cattle can be related positively to increases in farm size because farmers gaining more experience had more knowledge and skills available for solving problems on their farms [20,21].…”
Section: Demographic and Farm Characteristicsmentioning
confidence: 99%
“…It could be used as an evident that there was the great opportunity for farmers in the two villages to develop of cattle farming in order to generate income and produce manure to fertilize farm land, so that the whole farm was expected can improve the welfare for farmers. Widiati and Widi [2016] have been calculated that every cattle fattening could be done to generate income of IDR 3,545,309/AU within 4 months. It was became an opportunity and challenge for livestock farmers who were generally small scale and low capital, while to increase the scale of cattle farming requires additional capital.…”
Section: Carrying Capacity Of Forages For Cattle Developmentmentioning
confidence: 99%